The Effect of Green Tea Extract Supplementation and Different Catechol-O-Methyltransferase Genotypes on Plasma Catechins Concentrations in Women Who Are Post-menopause. (14th June 2022) - Tweel, Lauren; Radler, Diane Rigassio; Yang, Chung; Kurzer, Mindy; Samavat, Hamed
Abstract: Objectives: To determine if oral intake of green tea extract (GTE) capsules increases plasma concentrations of green tea catechins, and if genotypes impact changes in plasma concentrations of catechins. Methods: This study was a secondary analysis of the Minnesota Green Tea Trial (MGTT), a randomized, double-blind, placebo-controlled trial. Participants were healthy postmenopausal women receiving GTE capsules with 843.0 mg epigallocatechin gallate (EGCG) or placebo daily for 12 months. In a subset of the participants ( n  = 178) plasma concentrations of green tea catechins were analyzed at baseline and month 12. Absolute changes in concentrations of plasma catechins including EGCG, epigallocatechin (EGC), epicatechin gallate (ECG), and epicatechin (EC) were compared between treatment groups, and between COMT genotypes among those in the GTE group. Findings were stratified by potential confounding factors. Results: Participants were mainly white non-Hispanic with a mean ± SD age of 60.13 ± 5.14 years and BMI of 24.97 ± 3.76 kg/m 2 . Absolute changes from baseline in plasma concentrations of EGCG (46.32 vs. 0.00 nM), ECG (18.39 vs. 0.00 nM), and EC (15.56 vs 0.06 nM) were significantly higher in the GTE than the placebo group, respectively (all P s < 0.001). After adjusting for age and dietary intakes of fiber and vitamin C, absolute changes from baseline in plasma concentrations of EGCG were significantly greater in the high-activity COMT genotype ( G/G ) compared to those with the low-activity COMT genotypes ( A/A or A/G ) in the GTE group ( P  = 0.048). There was a statistically significant interaction between treatment and total vitamin C intake at baseline for absolute change from baseline of plasma EC ( Pint  = 0.008). Participants in the GTE group with vitamin C intake above median values at baseline experienced significantly greater positive increases in plasma concentration of EC compared to those in the placebo group. Conclusions: Concentrations of plasma EGCG, ECG, and EC were significantly increased after GTE supplementation for 12 months.  COMT  genotype may modify circulating EGCG concentrations; the entailed mechanism remains to be investigated. Funding Sources: NIH (Grant R01 CA127236).